Auditory habituation in the fetus and neonate: an fMEG study. Issue 2 (23rd February 2013) - Muenssinger, Jana; Matuz, Tamara; Schleger, Franziska; Kiefer‐Schmidt, Isabelle; Goelz, Rangmar; Wacker‐Gussmann, Annette; Birbaumer, Niels; Preissl, Hubert
Abstract: Habituation – the most basic form of learning – is used to evaluate central nervous system (CNS) maturation and to detect abnormalities in fetal brain development. In the current study, habituation, stimulus specificity and dishabituation of auditory evoked responses were measured in fetuses and newborns using fetal magnetoencephalography (fMEG). An auditory habituation paradigm consisting of 100 trains of five 500 Hz tones, one 750 Hz tone (dishabituator) and two more 500 Hz tones, respectively, were presented to 41 fetuses (gestational age 30–39 weeks) and 22 newborns or babies (age 6–89 days). A response decrement between the first and fifth tones (habituation), an increment between the fifth tone and the dishabituator (stimulus specificity) and an increment between the fifth (last tone before the dishabituator) and seventh tones (first tone after the dishabituator) (dishabituation) were expected. Fetuses showed weak responses to the first tone. However, a significant response decrement between the second and fifth tones (habituation) and a significant increment between the fifth tone and the dishabituator (stimulus specificity) were found. No significant difference was found for dishabituation nor was a developmental trend found at the group level. From the neonatal data, significant values for stimulus specificity were found. Sensory fatigue or adaptation was ruled out as a reason for the response decrement due to the strong reactions to the dishabituator. Taken together, the current study used fMEG to directly show fetal habituation and provides evidence of fetal learning in the last trimester of pregnancy. Abstract : Habituation ‐ the most basic form of learning ‐ is used to evaluate central nervous system (CNS) maturation and to detect abnormalities in fetal brain‐development. In the current study, habituation, stimulus specificity and dishabituation of auditory evoked responses were measured in fetuses and newborns using fetal magnetoencephalography (fMEG). An auditory habituation paradigm consisting of 100 trains of five 500Hz tones, one 750Hz tone (dishabituator) and two more 500Hz tones respectively were presented to 41 fetuses (gestational age 30‐39 weeks) and 22 newborns/babies (age 6‐89 days).